2021
DOI: 10.1002/ijfe.2534
|View full text |Cite
|
Sign up to set email alerts
|

Time‐varyingcausality between bond and oil markets of the United States: Evidence from over one and half centuries of data

Abstract: This paper analyzes time-varying causality between government bond and oil returns of the United States (US) over the monthly period of 1859:10 to 2019:03, i.e., the longest possible span of historical data, starting from the beginning of the modern era of the petroleum industry. While the standard constant parameter causality test fails to pick up any evidence of causality, the timevarying framework shows evidence of bi-directional spillovers over the entire sample period. The results are robust to inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…and Soytas (2018) too detected significant causality from the oil market to the high-yield bond market in terms of both price and volatility. 3 A working paper that must be mentioned is the work of Coronado, Gupta, Nazlioglu, and Rojas (2020). These authors used historical monthly data from the United States over the period 1859:10 to 2019:03 to detect time-varying evidence of bidirectional spillovers between oil and 10-year government bond returns, which is robust to the inclusion of stock returns as a control variable in the model.…”
Section: Discussionmentioning
confidence: 99%
“…and Soytas (2018) too detected significant causality from the oil market to the high-yield bond market in terms of both price and volatility. 3 A working paper that must be mentioned is the work of Coronado, Gupta, Nazlioglu, and Rojas (2020). These authors used historical monthly data from the United States over the period 1859:10 to 2019:03 to detect time-varying evidence of bidirectional spillovers between oil and 10-year government bond returns, which is robust to the inclusion of stock returns as a control variable in the model.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also found that there is generally a negative relationship between the two markets (Demirer and Gupta, 2018). However, there is a disagreement as to how the causality runs between the two markets with Coronado et al (2020) finding the causality to be bidirectional, while Nazlioglu et al (2020) finds a one-way causality from the bond market to the oil market and Nugyen et al (2018) and Balcilar et al (2020) finding the opposite direction.…”
Section: Literature Reviewmentioning
confidence: 96%
“…These studies have also found that there is generally a negative relationship between the two markets (Demirer and Gupta, 2018). However, there is a disagreement as to how the causality runs between the two markets with Coronado et al. (2020) finding the causality to be bidirectional, while Nazlioglu et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu hipotezin reddedilmesi, analiz döneminin tamamı için tüketici güven endeksinden enflasyon oranına doğru tek yönlü bir nedensellik ilişkisinin olduğunu göstermektedir. Arslanturk vd., 2011;Balcilar vd., 2010;Coronado, Gupta, Nazlioglu & Rojas, 2023;Tang, 2008;Wang, Su, Umar & Peculea, 2023). Yaşanan iktisadi ve politik gelişmeler ve gerçekleşen krizler, politika değişimleri, alınan iktisadi ve siyasi kararlar ile uluslararası gelişmeler değişkenler arasındaki ilişkileri zamanlar arasında değiştirebilmektedir 6 .…”
Section: Yöntem Ve Bulgularunclassified